Long-Term Outcomes and Prognostic Factors of Superficial Esophageal Cancer in Patients Aged ≥ 65 Years - Chang, Jin Won; Jung, Da Hyun; Huh, Cheal Wung; Park, Jun Chul; Shin, Sung Kwan; Lee, Sang Kil; Lee, Yong Chan (Frontiers in Medicine, 2022)
Background The number of elderly patients with superficial esophageal cancer (SEC) is increasing. We aimed to evaluate the clinical outcomes and prognostic factors of overall survival (OS) in elderly patients undergoing endoscopic submucosal dissection (ESD) or surgical resection for SEC. Methods Between January 2001 and May 2020, 290 patients aged ≥65 years who underwent ESD or surgical resection for SEC were evaluated. Their clinical outcomes and prognosis were assessed, and independent risk factors for OS were identified. Results The mean patient age (269 men and 21 women) was 70.9 years (range 65–90 years). En bloc, R0, and curative resections were achieved in 94.5%, 90.0%, and 73.4% of the patients, respectively. During the follow-up [mean: 54.6 months (range: 1–210 months)], 79 patients died. The 3-, 5-, and 10-year OS rates were 82.5, 73.1, and 59.7%, respectively. In multivariate analysis, cancer history of the other organs, American Society of Anesthesiologists performance status, and presence of lymphovascular involvement (hazard ratio = 1.852, 1.656, and 1.943, respectively; all P < 0.05) were independent risk factors for poor OS. The high-risk group (≥2 risk factors) showed a significantly lower OS than the low-risk group (≤ 1 risk factor) (P < 0.001). Conclusions The three risk factors could be useful in predicting the long-term prognosis of elderly patients with SEC.